Teachers' perception of the value of using computerized technologies in Professionnal Learning Community (PLC)in Francophone Africa: The case of Educational and Cultural Animation Cells in Sénégal - (:unkn) unknown (My University, 2023)
There are Educational and Cultural Animation Cells since the independence in Senegal. Similar to Professional Learning Communities (PLCs) or, more generally, Communities of Practice (CoPs), these groups of permanent or contractual teachers from one or more local elementary schools meet after classto discuss their teaching-learning practices, their difficulties and their successes. Since 2017, the Senegalese Ministry of Education and its international partners have wanted to revitalize the CAPCs in the Casamance region, in particular through integrating computerized technologies (IT), commonly known as digital technology. The Projet d'amélioration de l'é ducation de base en Casamance (PAEBCA) has enabled the CAPCs to be equipped with digital tablets and video projectors to film the teacher in the classroom (Diop and Wallet, 2017). Using an observation grid, they then analyze the projected film to improve the pedagogical approach and classroom practices. As part of an ongoing doctoral research project, we will attempt to provide some answers to the question: How is the use of computerized technologies perceived by teachers in Senegal's CAPCs? The initial results of the semi-directive interviews conducted with 21 teachers in Casamance show a varied use of tools and an institutional willingness to integrate technologies into the in-service training of teachers. The interviews also show a willingness on the part of teachers toremedy the difficulties of use, particularly through synchronous and asynchronous virtual distance exchanges, referred to here as multiplatform mobile applications (MMAs). Nevertheless, we observed a lack of reflexivity around the questions of instrumentation of practices for a true integration of technologies in the communities. This article aims to shed light on the underlying issues of computer-based technologies in Professional Learning Co
Keywords: African Research